PENGHIJAUAN MELALUI PENANAMAN BIBIT POHON DI DESA CIJERUK KECAMATAN MEKAR BARU - Permana, Angrian; Puspa, Rani; Hadi, Wahyudi Prasetyo; Fadhilah, Laila Nur (Yayasan Education and Social Center, 2025)
Reforestation is one of the important activities that must be carried out conceptually in dealing with environmental problems. Cijeruk Village is one of the villages that is quite good at responding to this reforestation activity. Tree planting is also a form of environmental preservation that needs to be cultivated. Reforestation and planting of seedlings are carried out with the aim of the community in Cijeruk Village. This community service activity was carried out in the Cijeruk area, Mekar Baru District, Tangerang Regency, with the aim of increasing public awareness of reforestation of the environment by planting trees. Planting on land on the side of the road was carried out together with village officials and the community, planting on empty plantation lands was carried out together with the community, while planting in residents' yards was carried out independently by the community. This activity received a very good response from the village officials and the community of Cijeruk Village which was the center of the activity location. Our hope is of course to make the community aware of the importance of tree planting activities to save water sources.